PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SUB TEMA KEANEKARAGAMAN HEWAN DAN TUMBUHAN BERBASIS TEORI BELAJAR KONSTRUKTIVISTIK UNTUK KELAS IV SEKOLAH DASAR - Titi Anjarini; Galih Yansaputra (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Technology development is very rapid which is marked by the increasing number of schools that use computers. This research is a development research with ASSURE model with steps: (1) analyzing student characteristics, (2) determining learning objectives, (3) choosing methods, materials, and strategies, (4) using materials, methods and strategies in learning, ( 5) involving students in learning, (6) evaluation. The results of the media expert test validation received a value of 94% (very valid). Material experts get a value of 95% (very valid). The results of the effectiveness test of the teacher got a score of 92%. For the results of individual trials on cognitive aspects got a score of 91%, on the affective aspect got a percentage of 84.3%, while in the psychomotor aspect got a percentage of 90.65%. In the field trial on the cognitive aspect, the percentage was 89%, while in the affective aspect the percentage was 92% and the psychomotor aspect was 87%. In this case the field trial shows a very effective level of effectiveness. The attractiveness aspect showed that the percentage of attraction obtained in the individual trials was 86% while the attraction aspect showed that the percentage of attraction in the field trial was 88%. From the results of the acquisition of motivation questionnaires both on individual and field tests showed very interesting criteria to be used in learning.Keywords: Multimedia, Sub Themes of Diversity of Animals and Plants,Constructivistic Learning Theory